149k views
5 votes

15 + 5x \\ 14x - 6

User Jolleyboy
by
5.1k points

1 Answer

2 votes

Reorder the terms:

6 + 14x = 15x

Solving

6 + 14x = 15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15x' to each side of the equation.

6 + 14x + -15x = 15x + -15x

Combine like terms: 14x + -15x = -1x

6 + -1x = 15x + -15x

Combine like terms: 15x + -15x = 0

6 + -1x = 0

Add '-6' to each side of the equation.

6 + -6 + -1x = 0 + -6

Combine like terms: 6 + -6 = 0

0 + -1x = 0 + -6

-1x = 0 + -6

Combine like terms: 0 + -6 = -6

-1x = -6

Divide each side by '-1'.

x = 6

Simplifying

x = 6


User Kai Inkinen
by
5.3k points